Vegetarian diets and risk of all-cause mortality in a population-based prospective study in the United States - Keeley Blackie; Gerd Bobe; Yumie Takata (BMC, 2023)
Abstract The popularity of vegetarian diets has increased the need for studies on long-term health outcomes. A limited number of studies, including only one study from a non-vegetarian population, investigated the risk of mortality with self-identified vegetarianism and reported inconsistent results. This study evaluated prospective associations between vegetarian diets and all-cause mortality among 117,673 participants from the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial cohort study. Vegetarian diet status was self-identified on the questionnaire. Deaths were ascertained from follow-up questionnaires and the National Death Index database. Multivariable Cox regression models were used to estimate the risk of all-cause mortality in hazard ratio (HR) and 95% confidence intervals (CI). By diet group, there were 116,894 omnivores (whose diet does not exclude animal products), 329 lacto- and/or ovo-vegetarians (whose diet excludes meat, but includes dairy and/or eggs), 310 pesco-vegetarians (whose diet excludes meat except for fish and seafood) and 140 vegans (whose diet excludes all animal products). After an average follow-up of 18 years, 39,763 participants were deceased. The risk of all-cause mortality did not statistically significantly differ among the four diet groups. Comparing with the omnivore group, the HR (95% CI) were 0.81 (0.64-1.03) for pesco-vegetarian group, 0.99 (0.80-1.22) for lacto- and/or ovo-vegetarian group and 1.27 (0.99-1.63) for vegan group, respectively. Similarly, mortality risk did not differ when comparing lacto- and/or ovo-vegetarians plus vegans with meat/fish eaters (omnivores and pesco-vegetarians) (HR [95% CI] = 1.09 [0.93-1.28]). As this study is one of the two studies of vegetarianism and mortality in non-vegetarian populations, further investigation is warranted.